2013
DOI: 10.1021/ja409223a
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant-Free Conversion of Primary Amines to Nitriles

Abstract: An amide-derived NNN-Ru(II) hydride complex catalyzes oxidant-free, acceptorless, and chemoselective dehydrogenation of primary and secondary amines to the corresponding nitriles and imines with liberation of dihydrogen. The catalyst system tolerates oxidizable functionality and is selective for the dehydrogenation of primary amines (-CH2NH2) in the presence of amines without α-CH hydrogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(82 citation statements)
references
References 69 publications
1
81
0
Order By: Relevance
“…CN bond dehydrogenation : In 2013, Szymczak and co‐workers reported the double dehydrogenation of amines to synthesize nitriles isolated in yields of 17–75 % 89. With their system, even sensitive compounds could be dehydrogenated selectively.…”
Section: Catalysis With Pincer‐type Catalystsmentioning
confidence: 99%
“…CN bond dehydrogenation : In 2013, Szymczak and co‐workers reported the double dehydrogenation of amines to synthesize nitriles isolated in yields of 17–75 % 89. With their system, even sensitive compounds could be dehydrogenated selectively.…”
Section: Catalysis With Pincer‐type Catalystsmentioning
confidence: 99%
“…[17][18][19][20] In this sense, the technological problems are minimized as the actuali nfrastructure is basedi nl iquidsf or storage and transport. [29] The viabilityo ft he amine/nitrile pair as ap otentialo rganic hydrogen carrier also lies in the effectiveness of the reverse process, that is, the hydrogenation of nitriles. [23][24][25][26][27] In this work, we have evaluatedt he potential of the amine/nitrile paira saliquid organic hydrogen carrier,a s suggested by Grelliera nd Sabo-Etienne in af rontier-type article (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, Hong and Muthaiah reported that ruthenium hydride complexes, such as RuH 2 (CO)(PPh 3 ) 3 and Shvo's complex, are also effective catalysts for the dehydrogenation of N‐containing heterocycles, under “acceptorless” and base‐free conditions . Later, a very interesting result was published by Szymczak's group where they demonstrated an amide‐derived NNN‐Ru II hydride complex catalyzes the oxidant‐free, acceptorless, and chemoselective dehydrogenation of primary and secondary amines to the corresponding nitriles and imines with the liberation of dihydrogen . However, dehydrogenation of amines with these ruthenium hydride complexes rely on the basic principle of hydrogen‐borrowing, and are mechanistically different from the aerobic oxidation of amines.…”
Section: Nitriles and Iminesmentioning
confidence: 99%